Yin and yang, or peas in a pod? Individual-sport versus team-sport athletes and altitude training. Issue 18 (19th November 2013) - Aughey, Robert J; Buchheit, Martin; Garvican-Lewis, Laura A; Roach, Gregory D; Sargent, Charli; Billaut, François; Varley, Matthew C; Bourdon, Pitre C; Gore, Christopher J
Abstract : The question of whether altitude training can enhance subsequent sea-level performance has been well investigated over many decades. However, research on this topic has focused on athletes from individual or endurance sports, with scant number of studies on team-sport athletes. Questions that need to be answered include whether this type of training may enhance team-sport athlete performance, when success in team-sport is often more based on technical and tactical ability rather than physical capacity per se. This review will contrast and compare athletes from two sports representative of endurance (cycling) and team-sports (soccer). Specifically, we draw on the respective competition schedules, physiological capacities, activity profiles and energetics of each sport to compare the similarities between athletes from these sports and discuss the relative merits of altitude training for these athletes. The application of conventional live-high, train-high; live-high, train-low; and intermittent hypoxic training for team-sport athletes in the context of the above will be presented. When the above points are considered, we will conclude that dependent on resources and training objectives, altitude training can be seen as an attractive proposition to enhance the physical performance of team-sport athletes without the need for an obvious increase in training load.